Older frail prehabilitated patients who cannot attain a 400 m 6-min walking distance before colorectal surgery suffer more postoperative complications. Issue 4 (April 2021) - Gillis, Chelsia; Fenton, Tanis R.; Gramlich, Leah; Sajobi, Tolulope T.; Culos-Reed, S. Nicole; Bousquet-Dion, Guillaume; Elsherbini, Noha; Fiore JR, Julio F.; Minnella, Enrico M.; Awasthi, Rashami; Liberman, A. Sender; Boutros, Marylise; et al.
Abstract: Introduction: Recent efforts to prehabilitate intermediately frail and frail (Fried frailty criteria ≥2) elective colorectal cancer patients did not influence clinical nor functional outcomes. The objective of this secondary analysis was to describe the subset of intermediately frail and frail prehabilitated patients who could not attain a minimum 400 m (a prognostic cut-point used in other patient populations) 6-min walking distance (6MWD) before elective surgery. Materials and methods: Secondary analysis of a randomized controlled trial. Patients participated in multimodal prehabilitation at home and in-hospital for approximately four weeks before colorectal surgery. Primary outcome was incidence of postoperative complications within 30 days of hospital discharge. Results: Sixty percent of the patients who participated in prehabilitation did not reach a minimum walking distance of 400 m in 6 min before surgery. Compared to the group that attained ≥400 m 6MWD (n = 19), the <400 m group (n = 28) were older, had higher percent body fat, lower physical function, lower self-reported physical activity, higher American Society of Anesthesiologists (ASA) classification, and twice as many were in critical need of a nutrition intervention at baseline. No group differences were observed regarding frailty status (P = 0.775). Sixty-one percent of the <400 m 6MWD group experienced at least one complication within 30 days of surgery compared to 21% in the ≥400 m group (P = 0.009). Conclusion: Several preoperative characteristics were identified in the <400 m 6MWD group that could be useful in screening and targeting future prehabilitative treatments. Future trials should investigate use of a 400 m standard for the 6MWD as a minimal treatment target for prehabilitation.